Novel XBP1s-independent function of IRE1 RNase in HIF-1α-mediated glycolysis upregulation in human macrophages upon stimulation with LPS or saturated fatty acid - Iovino, Margaud; Colonval, Megan; Wilkin, Chloé; L’homme, Laurent; Lassence, Cédric; Campas, Manon; Peulen, Olivier; de Tullio, Pascal; Piette, Jacques; Legrand-Poels, Sylvie (Frontiers in Immunology, 2023)
In obesity, adipose tissue infiltrating macrophages acquire a unique pro-inflammatory polarization, thereby playing a key role in the development of chronic inflammation and Type 2 diabetes. Increased saturated fatty acids (SFAs) levels have been proposed to drive this specific polarization. Accordingly, we investigated the immunometabolic reprogramming in SFA-treated human macrophages. As expected, RNA sequencing highlighted a pro-inflammatory profile but also metabolic signatures including glycolysis and hypoxia as well as a strong unfolded protein response. Glycolysis upregulation was confirmed in SFA-treated macrophages by measuring glycolytic gene expression, glucose uptake, lactate production and extracellular acidification rate. Like in LPS-stimulated macrophages, glycolysis activation in SFA-treated macrophages was dependent on HIF-1 activation and fueled the production of pro-inflammatory cytokines. SFAs and LPS both induced IRE1 endoribonuclease activity, as demonstrated by XBP1 mRNA splicing, but with different kinetics matching HIF1 activity and the glycolytic gene expression. Interestingly, both the knockdown of IRE1 and the pharmacological inhibition of its RNase activity prevented HIF-1 activation and significantly decreased glycolysis upregulation. Surprisingly, XBP1s appeared to be dispensable, as demonstrated by the lack of inhibiting effect of XBP1s knockdown on glucose uptake, lactate production and HIF-1 activation. These experiments demonstrate for the first time a key role of IRE1 in HIF-1-mediated glycolysis upregulation in macrophages stimulated with pro-inflammatory triggers like LPS or SFAs through XBP1s-independent mechanism. IRE1 could mediate this novel function by targeting other transcripts (mRNA or pre-miRNA) through a mechanism called regulated IRE1-dependent decay or RIDD. Deciphering the underlying mechanisms of this novel IRE1 function might lead to novel therapeutic targets to curtail sterile obesity- or infection-linked inflammation.